CYP2D6 Genetic Variation and Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis - Wannasuphoprasit, Yanisa; Andersen, Stig Ejdrup; Arranz, Maria J.; Catalan, Rosa; Jurgens, Gesche; Kloosterboer, Sanne Maartje; Rasmussen, Henrik Berg; Bhat, Anjali; Irizar, Haritz; Koller, Dora; Polimanti, Renato; Wang, Baihan; et al. (Frontiers in Psychology, 2022)
Background Antipsychotic-induced weight gain is a contributing factor in the reduced life expectancy reported amongst people with psychotic disorders. CYP2D6 is a liver enzyme involved in the metabolism of many commonly used antipsychotic medications. We investigated if CYP2D6 genetic variation influenced weight or BMI among people taking antipsychotic treatment. Methods We conducted a systematic review and a random effects meta-analysis of publications in Pubmed, Embase, PsychInfo, and CENTRAAL that had BMI and/or weight measurements of patients on long-term antipsychotics by their CYP2D6-defined metabolic groups (poor, intermediate, normal/extensive, and ultra-rapid metabolizers, UMs). Results Twelve studies were included in the systematic review. All cohort studies suggested that the presence of reduced-function or non-functional alleles for CYP2D6 was associated with greater antipsychotic-induced weight gain, whereas most cross-sectional studies did not find any significant associations. Seventeen studies were included in the meta-analysis with clinical data of 2,041 patients, including 93 poor metabolizers (PMs), 633 intermediate metabolizers (IMs), 1,272 normal metabolizers (NMs), and 30 UMs. Overall, we did not find associations in any of the comparisons made. The estimated pooled standardized differences for the following comparisons were (i) PM versus NM; weight = –0.07 (95%CI: –0.49 to 0.35, p = 0.74), BMI = 0.40 (95%CI: –0.19 to 0.99, p = 0.19). (ii) IM versus NM; weight = 0.09 (95% CI: –0.04 to 0.22, p = 0.16) and BMI = 0.09 (95% CI: –0.24 to 0.41, p = 0.60). (iii) UM versus EM; weight = 0.01 (95% CI: –0.37 to 0.40, p = 0.94) and BMI = –0.08 (95%CI: –0.57 to 0.42, p = 0.77). Conclusion Our systematic review of cohort studies suggested that CYP2D6 poor metabolizers have higher BMI than normal metabolizers, but the data of cross-sectional studies and the meta-analysis did not show this association. Although our review and meta-analysis constitutes one of the largest studies with comprehensively genotyped samples, the literature is still limited by small numbers of participants with genetic variants resulting in poor or UMs status. We need further studies with larger numbers of extreme metabolizers to establish its clinical utility in antipsychotic treatment. CYP2D6 is a key gene for personalized prescribing in mental health.